Climate : a new story - Eisenstein, Charles, 1967- (Berkeley North Atlantic books, 2018)
"Flipping the script on climate change, Eisenstein makes a case for a wholesale reimagining of the framing, tactics, and goals we employ in our journey to heal from ecological destruction With research and insight, Charles Eisenstein details how the quantification of the natural world leads to a lack of integration and our "fight" mentality. With an entire chapter unpacking the climate change denier's point of view, he advocates for expanding our exclusive focus on carbon emissions to see the broader picture beyond our short-sighted and incomplete approach. The natural and the material world--the rivers, forests, and creatures--are sacred and valuable in their own right, not simply for carbon credits or preventing the extinction of one species versus another. After all, when you ask someone why they first became an environmentalist, they're not likely to cite humanity's existential crisis, or our society going up in flames; they're likely to point to the river they played in, the ocean they visited, the wild animals they observed, or the trees they climbed when they were a kid. This refocusing away from impending catastrophe and our inevitable doom cultivates meaningful emotional and psychological connections and provides real, actionable steps to caring for the earth. Freeing ourselves from a war mentality and seeing the bigger picture of how everything from prison reform to saving the whales can contribute to our planetary ecological health, we resist reflexive postures of solution and blame and reach toward the deep place where commitment lives"--
"Flipping the script on climate change, Eisenstein makes a case for a wholesale reimagining of the framing, tactics, and goals we employ in our journey to heal from ecological destruction"--
Includes bibliographical references (pages 279-290) and index.
Keywords: Environmentalism; Environmental degradation -- Prevention; Climatic changes; Global environmental change; Nature -- Psychological aspects; Environmental psychology; NATURE / Environmental Conservation & Protection; BODY, MIND & SPIRIT / Inspiration & Personal Growth; POLITICAL SCIENCE / Public Policy / Environmental Policy